Chemical Process Safety : Learning from Case Histories - Sanders, Roy E. (Amsterdam : Butterworth-Heinemann, 2015)
"Chemical Process Safety: Learning from Case Histories, Fourth Edition gives insight into eliminating specific classes of hazards while also providing real case histories with valuable lessons to be learned. This edition also includes practical sections on mechanical integrity, management of change, and incident investigation programs, along with a list of helpful resources. The information contained in this book will help users stay up-to-date on all the latest OSHA requirements, including the OSHA-required Management of Change, Mechanical Integrity, and Incident Investigation regulations" --
"Butterworth-Heinemann is an imprint of Elsevier"--Colophon.
Keywords: Chemical processes -- Safety measures; Chemical industry; Risk analysis; Industrie chimique; Procedes chimiques; Analyse des risques; Prevention des accidents